Método dos elementos de contorno para elasticidade tridimensional - Curotto, Claudio Luiz (1981)
The boundary integral equation is obtained from the Betti's theorem of reciprocity. Body forces and thermal effects are considered in the forrnulation. Isoparametric elemnts of plane triangular shape with linear variation for the functions, define the boundary. The integrals over the elements are calculated by an analitical and numerical process. By the application of the discrete boundary integral equation on the boundary nodes, a linear system of equations is assembled. The unknows are the displacements and or the tractions, on the boundary. The systern of equations is solved by the Gauss triangularization method. Interior values for choosen nodes can be calculated from the Somigliana's Identity. The boundary stress tensors are obtained by the application of the Hooke' s law, using the boundary strains and tractions. Some examples are presented to examine the efficiency of the method and the results are compared with the Finite Element Method Solution.